Analyzing the correlation between gender variation and technology adaptation in language learning among foreign language students - Khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
The presence of technology in the domain of language education has proven to provide language learners with a plethora of opportunities to learn any language with ease. Language learners now use the technology of their choice to improve certain language skills. On the other hand, there are differences in the way male and female language learners use these technologies to achieve their required language learning goals. In this case, male language learners may choose a particular technology in language learning based on certain factors. This also applies to their female counterpart. The focus of this research anchors on analyzing this postulation in order to bring to the limelight the relevance of gender variation in technology adaptation in language education. Precisely, the objective of this research is to analyze the relationship between gender variation and technology adaptation in language learning among foreign language undergraduates. In the paper, a quantitative research methodology was adopted, wherein the research data were collated from a total number of three-hundred and ninety-four (394) foreign language undergraduates to achieve the objective of this research. However, relevant statistical measures such as CFA, descriptive statistics, and Pearson correlation were used to conduct proper analysis for the research. The results of the statistical analysis and the Pearson correlation test emphasize the critical role of gender in determining technology adaptation in language learning. Gender variation influences language learners’ acceptance (mean score =4.10), use of technology (mean score = 3.50), and perceptions of the effectiveness of technology (mean score =2.80). Meanwhile, the research concludes that gender variation influences language users’ acceptance of technology. However, when they accept it, there is a high tendency to use this technology in their language learning process and develop a positive perception of such technology.